Peran Poskamling dalam Meningkatkan Keamanan Desa Gagutur - Ricko Jordan Manuputty; Roma Nopitri; Penti, Penti; Asda Yetri Gustara; Friskila, Friskila; Genisya Veronika; Greisela Maria Adeice Korwa; Samara Eka Sinta; Lista Natalia; Sarina Wati; Bastian Sio; Loura Natasha Putri; Nickarter Haristama; Jessica Andriany; Dea, Dea; Gustina Rahayu (PT. ALHAFI BERKAH INDONESIA, 2024)
The Community Service Program (Kuliah Kerja Nyata or KKN) is a mandatory activity and a form of student service to the community, conducted as part of the educational process in higher education. The KKN Group 7 from the State Christian Institute of Palangka Raya was carried out in Gagutur Village, Gunung Bintang Awai Subdistrict, for approximately 40 days. During the implementation of the KKN, the group encountered various issues, including problems related to clean water, the provision of waste bins, and the security post (Pos Kamling) facility. However, the group's main focus was on the Pos Kamling facility, which became the priority in their work program. The Pos Kamling facility is a crucial element for maintaining the security of Gagutur Village, which consists of two neighborhood units (RT) with a significant population. The rehabilitation of the Pos Kamling is expected to meet the community's expectations in safeguarding the village environment. To ensure the smooth execution and success of the KKN activities, systematic and structured data management related to all aspects of the activities was essential. The outcomes of this work program are anticipated to provide a positive contribution not only in the short term but also for the sustainability of security and order in Gagutur Village.